2016
DOI: 10.18051/univmed.2015.v34.161-167
|View full text |Cite
|
Sign up to set email alerts
|

Seizure increases electroencephalographic abnormalities in children with tuberculous meningitis

Abstract: BACKGROUNDTuberculous meningitis (TBM) is a severe intracranial infection with fatal outcomes, permanent disabilities, and electroencephalographic (EEG) abnormalities. Seizures may occur in TBM. The EEG findings in TBM vary according to the site of the inflammatory process. There are few studies describing the EEG patterns and clinical manifestations of TBM. The objective of this study was to investigate the correlation between clinical findings and EEG patterns in children with TBM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
6

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 13 publications
0
5
0
6
Order By: Relevance
“…Focal spikes on EEG are more often associated with brain abnormalities that may induce recurrent seizures and chronic epilepsy [4]. Gunawan et al have found a strong correlation between clinical seizures and EEG abnormalities; this study has also reported that EEG can be used to detect seizure activity and assess the risk of epilepsy in patients with TBM [30]. Therefore, a severe and persistent epileptic activity on EEG may predict recurrent seizures and chronic epilepsy.…”
Section: Epileptic Activity On Eegmentioning
confidence: 60%
See 4 more Smart Citations
“…Focal spikes on EEG are more often associated with brain abnormalities that may induce recurrent seizures and chronic epilepsy [4]. Gunawan et al have found a strong correlation between clinical seizures and EEG abnormalities; this study has also reported that EEG can be used to detect seizure activity and assess the risk of epilepsy in patients with TBM [30]. Therefore, a severe and persistent epileptic activity on EEG may predict recurrent seizures and chronic epilepsy.…”
Section: Epileptic Activity On Eegmentioning
confidence: 60%
“…This study has also suggested that the presence of epileptiform discharges on EEG may predict chronic epilepsy [4]. Gunawan and colleagues have reported abnormal EEG activity in 75% of the patients, out of them 77% had epileptogenic activities; moreover, they found a strong correlation between epileptic spikes on EEG and the development of clinical seizures [30]. However, a recent study from China has concluded that the presence of epileptiform discharge on EEG was not associated with poorer outcome [75].…”
Section: Eeg Findingsmentioning
confidence: 83%
See 3 more Smart Citations